TALABALARDA BAXTLI OILA TO‘G‘RISIDAGI TASAVVURLAR SHAKILLANISHINING PSIXOLOGIK DETERMINATLARI - Abdurayimov, S.O. (SCIENCE and SOCIETY, 2024)
The article consists in determining the socio–psychological determinants of students ’ concepts about a sustainable family, which are aimed at the formation as a person in social relations, analyzing the typilogical features of identity and the state of study.